A universal role for MyD88 in TLR/IL-1R-mediated signaling. - Janssens, S.; Beyaert, R. (Trends in Biochemical Sciences, 2002)
The MyD88 adapter protein links members of the toll-like receptor (TLR) and interleukin-1 receptor (IL-1R) superfamily to the downstream activation of nuclear factor-kappaB and mitogen-activated protein kinases. Although originally identified as a myeloid-differentiation marker, MyD88 is now known to play an essential role in the innate immune response of insects and mammals. The generation of MyD88-deficient mice, as well as the identification of MyD88-related proteins and regulators of MyD88 signaling, has revealed new and important insights into the function of MyD88.